An Interdisciplinary Approach to Study the Fouling Phenomenon. (December 2015) - Aldi, Nicola; Morini, Mirko; Pinelli, Michele; Spina, Pier Ruggero; Suman, Alessio
Abstract: Solid particle ingestion is one of the principal degradation mechanisms in the compressor section of heavy-duty gas turbines. Foulants in the ppm range which are not captured by the air filtration system usually cause deposits on blading, which results in a severe drop in the performance of the compressor.Through the interdisciplinary approach proposed in this paper, it is possible to determine the evolution of the fouling phenomenon through the integration of several studies in different research fields: (i) numerical simulation, (ii) power plant characteristicsand (iii) particle-adhesion characteristics.This paper shows the possibility of linking the numerical results related to the impact/adhesion characteristic of the particles with the actual air contamination data and operating condition of the power units. In fact, the size of the particles, their concentrations and the filtration efficiency represent the major contributors to performing a realistic quantitative analysis of the fouling phenomena in an axial compressor.The integration of these research fields could represent a valuable support for the investigation of the relationship between compressor airfoil design and fouling rate.